2018
DOI: 10.3892/ijmm.2018.3552
|View full text |Cite
|
Sign up to set email alerts
|

PEDF improves cardiac function in rats subjected to myocardial ischemia/reperfusion injury by inhibiting ROS generation via PEDF‑R

Abstract: The prevention and management of myocardial ischemia/reperfusion (MI/R) injury is an essential part of coronary heart disease surgery and is becoming a major clinical problem in the treatment of ischemic heart disease. Previous studies by our group have demonstrated that pigment epithelium-derived factor (PEDF) improves cardiac function in rats with acute myocardial infarction and reduces hypoxia-induced cell injury. However, the protective function and mechanisms underlying the effect of PEDF in MI/R injury r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Indeed, EGCG inhibits the activities of NADPH oxidase [ 83 ] and ERK1/2 via 67LR [ 75 , 84 ]. PEDF also abrogates ERK1/2 and NADPH oxidase activities [ 85 , 86 , 87 ]. Thus, our findings suggest that EGCG and NU335 may lead to astroglial AQP4 upregulation by 67LR-medaited NADPH oxidase inhibition, which would decrease ERK1/2-AKT activities.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, EGCG inhibits the activities of NADPH oxidase [ 83 ] and ERK1/2 via 67LR [ 75 , 84 ]. PEDF also abrogates ERK1/2 and NADPH oxidase activities [ 85 , 86 , 87 ]. Thus, our findings suggest that EGCG and NU335 may lead to astroglial AQP4 upregulation by 67LR-medaited NADPH oxidase inhibition, which would decrease ERK1/2-AKT activities.…”
Section: Discussionmentioning
confidence: 99%
“…PEDF is associated with signaling pathways related to cancer development. PEDF can directly bind to PEDF receptor (PEDFR) and stimulate the activity of phospholipase (26). PEDFR is strongly linked to cell proliferation in cancers (27).…”
Section: Discussionmentioning
confidence: 99%
“…However, myocardial ischemia-reperfusion (I/R) injury (MIRI) may result in additional cardiomyocyte dysfunction, which further aggravates myocardial cell damage (3), and constitutes a significant part of the pathology, contributing to heart failure in patients with CHD (4). The mechanisms underlying MIRI are complex and are associated with a variety of pathologies, such as oxidative stress, calcium overload, inflammatory response and energy metabolism disorders (4)(5)(6). Among these contributors, a number of studies have demonstrated that oxidative stress induced by a rapid increase in the levels of reactive oxygen species (ROS), which can be observed during reperfusion, is a key initiator of MIRI (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms underlying MIRI are complex and are associated with a variety of pathologies, such as oxidative stress, calcium overload, inflammatory response and energy metabolism disorders ( 4-6 ). Among these contributors, a number of studies have demonstrated that oxidative stress induced by a rapid increase in the levels of reactive oxygen species (ROS), which can be observed during reperfusion, is a key initiator of MIRI ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%